The economics of globally shared and public goods - Seo, Sungno Niggol (London, United Kingdom ; San Diego, CA, United States : Academic Press, is an imprint of Elsevier, 2020)
"The Economics of Globally Shared and Public Goods responds to an urgent need to consolidate and refine the economic theories and explanations pertinent to globally shared resources. Making a clear distinction between theories and empirical models, it elucidates the problem of global public goods while incorporating insights from behavioral economics. Its comprehensive and technical review of existing theoretical models and their empirical results illuminate those models in practical applications. Relevant for economists and others working on challenges of globally shared goods such as climate change and global catastrophes, The Economics of Globally Shared and Public Goods provides a path toward greater co-operation and shared successes."--Back cover.
Includes bibliographical references and index.
Keywords: Public goods -- Economic aspects; Public goods -- International cooperation